Wildfire promotes the invasion of Robinia pseudoacacia in the unmanaged Mediterranean Castanea sativa coppice forests - Saulino, Luigi; Rita, Angelo; Stinca, Adriano; Liuzzi, Greta; Silvestro, Roberto; Rossi, Sergio; Saracino, Antonio (Frontiers in Forests and Global Change, 2023)
In the Mediterranean region of southern Europe, Castanea sativa Mill. (Castanea) coppice stands are being invaded by non-native pioneer tree species due to recurrent coppicing and wildfire disturbances. There is a need to control the spread of non-native tree species in Castanea coppices due to their pivotal socio-economic role, however, to facilitate this, further research into invasive strategies and their interactions with disturbances is required. The non-native Robinia pseudoacacia L. (Robinia) has widely colonized the overaged and unmanaged Castanea coppice forests in Vesuvius National Park, which were disturbed by the low-severity fires in the summer of 2017. Here, we aimed to assess the functional traits conferring a competitive advantage to the Robinia over Castanea and the changes in spatial stand patterns driven by wildfire disturbance. To achieve this we assessed the spatial stem patterns, regeneration strategies, and conducted field-assessments and remote sensing of the spring leaf phenology of both Castanea and Robinia in five 300–600 m2 plots. After the 2017 wildfire, root suckers constituted 72% (± 12) of the Robinia vegetative living sprouts and occurred up to a distance of 10 m from the adult parent trees under the canopy of the Castanea trees. NDVI-based estimates at the start of the growing season (sos) in Castanea occurred over a 7 day period, from DOY 118–124, increasing at a rate (rsp) of 0.10–0.16, in agreement with the field-based assessment of spring leaf phenology. In Robinia, the sos estimated at DOY 109 from the NDVI seasonal trajectory disagreed with the field-based observations, which started later than Castanea, after approximately DOY 133. Here, the high percentage cover ( 90%) of the understory species influenced NDVI-based estimates of Robinia leaf spring phenology. The results suggest that low-severity wildfires increased the invasiveness of Robinia, and that vegetative regeneration strategies, rather than earlier spring phenology, conferred a competitive advantage in the fire-disturbed Castanea coppice stands. The results thus suggest that appropriate management of invasive Robinia trees to conserve the continuous canopy cover of Castanea stands should guide nature-based solutions to control the spread of non-native tree species.